Recent advances in understanding and managing hairy cell leukemia - Roider, Tobias; Falini, Brunangelo; Dietrich, Sascha (F1000Research, 2018)
Hairy cell leukemia is a rare B-cell malignancy that is characterized by an indolent course. It was initially described as a distinct entity in 1958. Before the establishment of modern treatment, median survival was only 4 years. Since then, major advances in the treatment and understanding of the biology and genomic landscape of hairy cell leukemia have been made. This review summarizes the present understanding of hairy cell leukemia with particular focus on the development of novel and targeted approaches to treatment.
Gesehen am 10.04.2019